A Study Of The Rationale For The Provision Of Education By The Charismatic Churches In Ghana: The Case Study Of Three Selected Churches - Frakue-Quarshie, J.S. (University of Ghana, 2017)
The focus of this thesis has been to investigate the rationale for the provision of education by three selected Charismatic churches in Ghana – the Full Gospel Church International (FGCI), the International Central Gospel Church (ICGC) and the Action Chapel International (ACI). It discussed and examined the factors responsible for the generation of interest by the selected charismatic churches in the provision of education in Ghana. Particularly, the charismatic churches have been seen to be “experiential” by nature and so have been preoccupied with addressing the spiritual needs of its members while little interest have been demonstrated by them in the social economic needs of their members at their emergence on the Christian landscape of Ghana. However, three decades ago, the Charismatic churches began to show interest in the provision of education in Ghana. The historical approach and phenomenological method of data gathering were employed. Interviews, participant observation, books and other print materials were consulted. Internet resources were also used. Heads of selected churches, administrators of the schools established by these churches were interviewed; school children as well as parents were also interviewed. The findings of this research identified a number of reasons that informed the provision of education by these charismatic churches. It was found out that these charismatic churches‟ interest in the provision of education is evangelization, responding to educational needs of Ghana, prestige and profit. Among some recommendations made is the fact that, in as much as the charismatic churches are not to neglect the intellectual and academic development of their pupils and students, more attention and impetus should be brought to bear on the Christian up bringing aspect of their provision of education.
Thesis (MPhil)